IMPLEMETASI ADAB DAN SOPAN SANTUN BERBAHASA DALAM PEMBENTUKAN KARAKTER ANAK - Inawati, Inawati (LPPM STKIP PGRI Bandar Lampung, 2018)
Etiquette and manner of speaking reflected in the way of communicating by verbal or the way how to communicate. Etiquette of speaking is very important to pay attention by participants (communicator and communication) for fluency communication. Therefore, this language problem ettiquete should get the attention, especially the use of language in daily life. Speaking politeness describe politeness of the speaker. Ettiquete a child in speaking usually imitate the habit of his parents in speaking daily life. Sometimes parents inadvertently or accidentally often express the words or phrases that are not good to be heard by children. In this case the application needs to be civilized and polite language as an effort to build the character. Things that need to be done in building a child character are as follows. (1) Parents are accustomed to use polite language when communicating with children. (2) Parents should avoid taboo words. (3) Parents should seek to use fine words (euphemism). (4) Parents should try to choose the honorifics. (5) Parents should establish good relationship with teachers at the school to determine the personality development of their children.